Ophiogomphus tibeticus sp. nov. from Sichuan, China (Anisoptera: Gomphidae) - Yu, Xin; Li, Linyan; Gu, Haijun (Zootaxa, 2022)
A new gomphid species, Ophiogomphus tibeticus sp. nov., from Zoige alpine Wetland, Sichuan is described and illustrated. Assignment to the genus Ophiogomphus Selys, 1854 is based on both morphological and molecular analyses. This new species differs from other known Ophiogomphus mainly in the shape of the caudal appendages.